[Rev.] Precarious Employment: Origins, Criteria, Features. Ed. by Zh.T. Toshchenko. Moscow: Ves Mir publ., 2021 - Ivan I. Osinsky; Marina I. Dobrynina (Социологический журнал, 2022)
The review discusses the results of the collective efforts of researchers to understand problems associated with precarious employment, its origins, criteria and features. The originality of the concept, its relevance and significance for modern science and social practice are revealed. It is shown that in modern conditions the precarious state of workers carries over to their entire way of life.